Prosecuting corporations for genocide - Kelly, Michael J., 1968- (New York, NY : Oxford University Press, 2016)
In this age of globalization, multinational corporations have risen to become the dominant actors on the world stage. They increasingly invest in the developing world and, in so doing, sometimes become complicit, financially and otherwise, in genocides that occur in there. While corporations can realize enormous profits from such complicity, they are immune from international prosecution in The Hague. This book proposes new legal pathways to prosecute multinational corporations by creating a framework for international criminal jurisdiction.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 28, 2016).
Keywords: Tort liability of corporations; Criminal jurisdiction; Jurisdiction (International law); Crimes against humanity; Genocide; Corporate governance -- Law and legislation; Law